The Effectiveness Of Awig-Awig On Merariq Age Maturation In Prevention Of Early Marriage In Kekait Village - Hamdi Hamdi; Fitriani Amalia; Sahrul Sahrul (Unram Law Review, 2022)
Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage Article 7 reads, "marriage is only allowed if a man and woman have reached the age of 19 (nineteen) years". In the new law, the age requirement is 19 years for the two prospective brides. While the age of marriage in the previous law, namely Law Number 1 of 1974 concerning Marriage in Article 7 paragraph (1), it is stated that "marriage is only allowed if the man has reached the age of 19 years of marriage and the woman has reached the age of 16 years. Merariq in the Sasak community is difficult to avoid because it is a hereditary tradition, as well as in Kekait Gunungsari Village, District, West Lombok Regency. Merariq in Kekait village is a regular marriage. In fact, almost all marriages are carried out with merariq. Merariq in Kekait village leaves social problems, such as easy divorce, stunting, early marriage, and school-age marriage. School-age marriage and early marriage are the focus of the Kekait Village Government which must be prevented through village regulations or awig-awig on the maturation of the age of merariq. This awig-awig regulates the merariq procedure, starting from the minimum age for merariq, farewell to the bride and groom who have not reached the minimum age requirement, school-age marriage, to sanctions for those who marry early. Sanctions are also given to village officials directly involved in early marriage.